Investigation of English Communication Skills of University Students - Abbasi, Abdul Malik; Mangrio, Riaz Ahmed; Channa, Mansoor Ahmed; Hanif, Urooj (International Journal of Publication and Social Studies, 2020)
This study aims to explore the factors affecting English spoken abilities of university level students who face problems in speaking adequate English. English is used in Pakistan as a professional tool, however, it is taught as a subject rather than a language that is the reason even at the university level, Pakistani students face problems in speaking English properly. The study further examines the impact of English speaking skills on one’s career and personality and to investigate different attainable ways for the students to develop their speaking skills. For this purpose, the total number of samplings (N=40) undergraduate respondents from different universities of Karachi were randomly preferred as a Sample of the study in which there were (n=18) males and (n=22) females under the age limit of 18 to 22. The study was based on online closed-ended questionnaire. Online Google Questionnaire form was utilized as a data collection tool. The study revealed that majority of the students face problem in speaking fluent English while they wish to be the fluent speakers. Additionally, the study found some phonetic and cognitive aspects i.e., pronunciation, grammar, listening and reading are important factors they face. The study further discovered different techniques for the students to develop their oral skills on their own. The improvement of English speaking builds up the confidence level of students which ultimately helps them to achieve successful career opportunities ahead.